International Migration and Household Well-Being : Evidence from Uzbekistan - Seitz, William (World Bank, Washington, DC, 2019)
As one of the most pivotal ways that labor markets adjust to changing economic conditions, international migration is never far from the center of the national discussion in Uzbekistan. This paper summarizes the relationship between recent international migration trends and household well-being using a combination of administrative records and unique panel survey data from the Listening to the Citizens of Uzbekistan study. The panel design provides data on changes in well-being leading up to and following a migrants' departure. This feature enables analysis that controls for unobserved time-invariant respondent and location characteristics. The findings show that weak local labor markets drive labor migration from Uzbekistan. Beginning to consider migration is associated with low life satisfaction, job loss, and unemployment. In contrast, actually migrating is associated with a remarkable improvement in labor market outcomes, alongside strong recovery in subjective and monetary measures of household welfare. The results further show that current migrants are more likely to send remittance payments when household members have deteriorating life satisfaction and/or subjective reports of worsening economic conditions at home. In the absence of remittance income, the poverty rate in Uzbekistan (measured at $3.2/day purchasing power parity) would be expected to rise from 9.6 to 16.8 percent, or to about 12.2 percent assuming (implausibly) that all current migrants were to find formal employment at the local prevailing median wage.